Institutional infrastructure and economic growth in member countries of the Organization of Islamic Cooperation (OIC) - Slesman, Ly; Baharumshah, Ahmad Zubaidi; Ra'ees, Wahabuddin Sahibuddin (Elsevier, 2015)
This paper examines the relationship between quality of different dimension institutional infrastructure and economic growth in a panel of 39 Organization of Islamic Countries (OIC). the empirical results confirm that the better-quality political and economic institution can have positive effects on on economic growth. All in all, the evidence fro the nonlinear model reveals that the quality of political institutions that ensure stable government, less expropriation, and low external conflict are the core dimensions of an institutional matrix because they influence the growth effects of economic institutions, confirming the "hierarchy of institutions hypothesis." the study also find that when political and economic institutions are accounted for, institutions that prevent internal conflict and tensions arising from ethnic and religious conflicts do not have significant (positive)impacts on growth. This institutional reforms to upgrade the of both political and economic institutions are crucial for development in OIC countries.